Prevalence and predictors of gaps in care among adult congenital heart disease patients: HEART-ACHD (The Health, Education, and Access Research Trial) - Gurvitz, Michelle; Valente, Anne Marie; Broberg, Craig; Cook, Stephen; Stout, Karen; Kay, Joseph; Ting, Jennifer; Kuehl, Karen; Earing, Michael; Webb, Gary; Houser, Linda; Opotowsky, Alexander; et al. (Journal of the American College of Cardiology, 2013)
The goal of this project was to quantify the prevalence of gaps in cardiology care, identify predictors of gaps, and assess barriers to care among adult congenital heart disease (adult CHD) patients. Adult CHD patients risk interruptions in care that are associated with undesired outcomes. Patients (18 years of age and older) with their first presentation to an adult CHD clinic completed a survey regarding gaps in, and barriers to, care. Among 12 adult CHD centers, 922 subjects (54% female) were recruited. A >3-year gap in cardiology care was identified in 42%, with 8% having gaps longer than a decade. Mean age at the first gap was 19.9 years. The majority of respondents had more than high school education and knew their heart condition. The most common reasons for gaps included feeling well, being unaware that follow-up was required, and complete absence from medical care. Disease complexity was predictive of a gap in care with 59% of mild, 42% of moderate, and 26% of severe disease subjects reporting gaps (p < 0.0001). Clinic location significantly predicted gaps (p < 0.0001), whereas sex, race, and education level did not. Common reasons for returning to care were new symptoms, referral from provider, and desire to prevent problems. Adult CHD patients have gaps in cardiology care; the first lapse commonly occurred at age ∼19 years, a time when transition to adult services is contemplated. Gaps were more common among subjects with mild and moderate diagnoses and at particular locations. These results provide a framework for developing strategies to decrease gaps and address barriers to care in the adult CHD population.